Respuesta :
[tex]-6=\frac{2}{9}x\\ \\ -6*\frac{9}{2}=x \\ \\ -27=x[/tex]
Hope this helps!
For this case we have the following equation:
[tex] -6 =\frac{2}{9}x [/tex]
From here, we must clear the value of x.
For this, we follow the following steps:
1) Place the 9 multiplying:
[tex] -6 (9) = 2x [/tex]
[tex] -54 = 2x [/tex]
2) Place the 2 dividing:
[tex] -\frac{54}{2} = x [/tex]
[tex] -27 = x [/tex]
3) Rewrite the result:
[tex] x = -27 [/tex]
Answer:
The result of the equation is:
[tex] x = -27 [/tex]